Organic vis-à-vis Natural Farming - Relevance to Indian Scenario - Bhaduri, Debarati; Saha, Soumya; Verma, B. C. (Chronicle of Bioresource Management, 2023)
In recent times, agriculture has become the center of all the life-changing arguments related to the environment, water, biodiversity etc., that collectively determine the future of our planet. The use of high amount of chemical inputs (agrochemicals etc.) is often required to enhance the agricultural productivity to feed the increasing population. But slowly this is leading to deterioration of the agricultural ecosystem and increase in the cost of production. Organic and natural farming can solve the issue to a significant extent by minimizing the over-dependence of high input agriculture, harnessing the natural resources to a large extent and maintaining the agricultural ecosystem. The present article deals with components, environmental advantage and socio-economic benefits of organic vis-à-vis natural farming, as compared to conventional and chemical-based farming. The other policy level interventions and India’s current status on natural farming was also discussed.